Dynamics of photogenerated holes in undoped BiVO4 photoanodes for solar water oxidation - Ma,Y; Pendlebury,SR; Reynal,A; Le,Formal F; Durrant,JR (Chemical Science, 2014)
The dynamics of photogenerated holes in undoped BiVO4 photoanodes for water splitting were studied using transient absorption spectroscopy, correlated with photoelectrochemical and transient photocurrent data. Transient absorption signals of photogenerated holes were identified using electron/hole scavengers and applied electrical bias in a complete photoelectrochemical cell. The yield of long-lived (0.1-1 s) photogenerated holes is observed to correlate as a function of applied electrical bias with the width of the space charge layer, as determined by electrochemical impedance spectroscopy. The transient absorption decay time constant of these long-lived holes is also observed to be dependent upon the applied bias, assigned to kinetic competition between water oxidation and recombination of these surface accumulated holes with bulk electrons across the space charge layer. The time constant for this slow recombination measured with transient absorption spectroscopy is shown to match the time constant of back electron transfer from the external circuit determined from chopped light transient photocurrent measurements, thus providing strong evidence for these assignments. The yield of water oxidation determined from these measurements, including consideration of both the yield of long-lived holes, and the fraction of these holes which are lost due to back electron/hole recombination, is observed to be in good agreement with the photocurrent density measured for BiVO4 photoanodes as a function of bias under continuous irradiation. Overall these results indicate two distinct recombination processes which limit photocurrent generation in BiVO4 photoanodes: firstly rapid ([less-than-or-equal]microseconds) electron/hole recombination, and secondly recombination of surface-accumulated holes with bulk BiVO4 electrons. This second 'back electron transfer' recombination occurs on the milliseconds-seconds timescale, and is only avoided at strong anodic biases where the potentia